Occupational therapists’ experiences of photo-supported conversations – An intervention in primary health care - Joanna Nordstrand; A. Birgitta Gunnarsson; Petra Wagman; Ulrica Hörberg; Kristina Holmgren (Scandinavian Journal of Occupational Therapy)
Background The health-promoting intervention BeWell™, which includes photo-supported conversations, is intended for people with stress-related illnesses. Its focus is on improving the individual’s health and well-being by addressing what contributes to well-being from the patient’s own perspective. There is no current knowledge of the experiences of occupational therapists of using BeWell™ in primary health care. It is thus important to gain knowledge of their experiences of using this intervention as part of investigating its feasibility.Aim To describe the occupational therapists’ experiences of photo-supported conversations about well-being (BeWell™) with patients diagnosed with stress-related illnesses.Material and methods Six occupational therapists, working in primary health care, who had conducted the photo-supported conversations about well-being (BeWell™), were interviewed individually, and one focus group discussion was also conducted. Systematic text condensation was used as the analysis method.Results Three main themes with two to three subgroups in each were identified; Discovering well-being through images, Enhancing patient’s own efforts towards well-being, and Contributing to one’s own well-being.Conclusions and significance The results provide important knowledge for the continued research work with BeWell™ by investigating how the users of the intervention experienced it.